MyReflections for CEEC221 PPKA / Hazrina Ahmad, Md Rasul Mohamad Noor and Noor Syafeekha Mohamad Sakdun - Ahmad, Hazrina (Unit Penerbitan FKAPP, 2023)
Starting from Semester March – August 2022 (20222), to fulfill the EAC accreditation requirement to get students feedback on their attainments, the OBE Unit of PKA UiTMCPP has taken an initiative in developing the MyReflections System via the PPKA website. This simple medium is developed allowing the students to give feedbacks on their PO attainment to the center of study The flow of the MyReflections for every semester is as shown in Figure 1. At the beginning of the semester, a face-to-face meeting will be carried out with all PPKA both new and old students. Briefing will be given by the KPP, and KP’s from both Diploma and Degree program. This is followed by students meeting with their Academic Advisors to discuss on academic matters and their PO attainment. This process is followed by the feedback of the students through MyReflections. Students may view their own PO attainment via PPKA website. The cumulative PO attainment is presented in spiderweb as well the PO for each subject. A sample of the MyReflections interface